Factors Contributing to the Waste Generation in Building Projects of Pakistan - Memon, Nafees Ahmed; Laghari, Muhammad Aslam; Memon, Fareed Ahmed (Mehran University Research Journal of Engineering and Technology; Vol 35 No 1 (2016): January Issue, 2016)
Generation of construction waste is a worldwide issue that concerns not only governments but also the building actors involved in construction industry. For developing countries like Pakistan, rising levels of waste generation, due to the rapid growth of towns and cities have become critical issue. Therefore this study is aimed to detect the factors, which are the main causes of construction waste generation. Questionnaire survey has been conducted to achieve this task and RIW (Relative Importance Weight) method has been used to analyze the results of this study. The important factors contributing to the generation of construction as identified in this study are: frequent changes/ revision in design during construction process; poor scheduling; unavailability of storage; poor workmanship; poor layout; inefficient planning and scheduling of resources and lack of coordination among supervision staff deployed at site. Based on the identified factors, the study also has presented some suggestions for the reduction of construction waste in building construction projects of Pakistan.